Media, Secret Ballot and Democratization in the US (2020)
Can the media determine the success or failure of institutional reforms? We study the adoption of secret voting in the US and the role of media in this arguably crucial step to improve democracy. Using a difference-in-difference identification strategy and a rich dataset on local newspapers, we find that in areas with high levels of media penetration democratization outcomes improved following the adoption of the secret ballot. Specifically, the press contributed to the decrease in partisan attachment and support for dominant parties. The press also undermined the manipulation of electoral boundaries and the unintentional decline in turnout incentivized with the introduction of the secret ballot. We consider multiple concerns about our identification strategy and address the potential endogeneity of newspapers using an instrumental variable approach that exploits the introduction of wood-pulp paper technology in 1880 combined with counties¿ woodland coverage during the same period. Exploring the heterogeneous effects of our results, we argue that the media mattered through the distribution of information to voters and the increase of public awareness about political misconduct.